(3BjGJ GdCMcGes - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s
(3ChdgG (B:s
... (3LhGHG ddTQW Hd YGWaI Ydi cfJe dCf de JbdH GdeVGQY eGVjG hJfajg Hd GdLhGH (B.. (3hGdeYfi ade JJecfhG ef GSJYeGd GdeGA dCf GdeefhY ef GdTjA cGdaGbO dg aJjeehG Cj aJYeOhG hGbUOhG UYjOG Cj TjFG Ydi hLg GdCQV (B..s
(3BNQgG (B:s
.. (3GdNGeSI hGeSMhG HQDhSce ; bjd GdHGA ddJHYjV dCfg GdaGQb Hjf eSMJ HGdefOjd heSMJ GdefOjd hbjd RGFOI dCf GdeSM jJYO HfaSg hdPdc CfcQ Cgd GdYQHjI GaGOJ GdJHYjV hGdJMbjb CfgG JOd Ydi JVejf GdaYd (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\282s
(3GdPQjYI (B18\1184s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs